Strategy of Information Exchange Found in Bird Box (2018) - Puji Laksono; Desta Lifia Riadhus Sholikhah (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
Communication involves strategy of information exchange. There are many strategies. In this paper, it will be discussed types of strategy used by speaker and hearer in order to exchange information in Bird Box . Theory used as basics for analyzing data is speech act. Data were collected by observation. The steps were watching movie and reading the scripts, identifying the data, and classifying the data. Researcher also applies the procedure to analyze data; displaying, selecting, explaining, interpreting data and making conclusion. The results show that there are four strategies of information exchange that used by the main character when they do communication: direct speech act provoked by direct speech act, indirect speech act provoked by direct speech act, direct speech act provoked by indirect speech act, and indirect speech act provoked by indirect speech act.